Грамматические средства моделирования тропов как продуктивные репрезентанты оценочных значений в современном украинском языке: лексико-грамматический оксюморон - Vladimirovna Khaliman, Oksana (Slavia Centralis, 2020)
The features of modeling lexico-grammatical oxymorons to express axiological nuances of meanings in Ukrainian are described in the article. The mechanisms of forming linguistic units on the basis of the conflicting compatibility of lexical and grammatical semantics are characterised: singularity/plurality; plurality/the singular; non-graded feature/degree of expression of a feature; procedural, duration of an action/its limit. The particular performance in terms of expressing evaluation among the types described is characterised by the formation of multiple singular forms and creative modeling of the forms of the degrees of comparison.